2019
DOI: 10.1038/s41467-019-13579-3
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation and alkylation stresses activate ribosome-quality control

Abstract: Oxidation and alkylation of nucleobases are known to disrupt their base-pairing properties within RNA. It is, however, unclear whether organisms have evolved general mechanism(s) to deal with this damage. Here we show that the mRNA-surveillance pathway of no-go decay and the associated ribosome-quality control are activated in response to nucleobase alkylation and oxidation. Our findings reveal that these processes are important for clearing chemically modified mRNA and the resulting aberrant-protein products.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 94 publications
1
82
0
Order By: Relevance
“…As a result, numerous alkylated nucleosides can be generated in RNA, possibly affecting the RNA structure and/or the protein-coding potential of mRNA. A recent study even showed that alkylated mRNA is subject to rapid degradation via NGD 12 . Finally, the presence of internal N 7methylguanosine (m 7 G) in mRNA is known to promote translation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, numerous alkylated nucleosides can be generated in RNA, possibly affecting the RNA structure and/or the protein-coding potential of mRNA. A recent study even showed that alkylated mRNA is subject to rapid degradation via NGD 12 . Finally, the presence of internal N 7methylguanosine (m 7 G) in mRNA is known to promote translation.…”
Section: Discussionmentioning
confidence: 99%
“…The oxidation of mRNA affects multiple steps of mRNA fate determination, including mRNA stability and translation 12,[70][71][72][73] . For instance, the oxidation of mRNA (typically 8-oxoG) inhibits the efficiency of peptide bond formation by >1000-fold, regardless of the codon position 71 .…”
Section: -Oxo-78-dihydroguanosinementioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned before, oxidative stress can impact translation at several steps of the process, including initiation, elongation, and quality control [50,164,165]. Recent work by the Zaher lab showed that RNA alkylating and oxidizing agents, MMS and 4-NQO, respectively, can lead to ribosome stalling and increased Ltn1-dependent ubiquitination of the arrested peptide, in addition to ubiquitination of ribosomal proteins mediated by the RQC E3 Hel2 [194]. Therefore, RTU and RQC pathways seem to be important to control specific subpopulations of ribosomes that might arise depending on the intensity of the stress, its duration, and the chemical nature of the reactive oxygen species employed.…”
Section: Overview Of Redox Control Of Translation By Ubiquitin (Rtu) mentioning
confidence: 96%
“…Oxidative modifications of mRNA can also impair base pairing within RNA and are capable of triggering ribosome quality control pathways [156]. Although oxidized mRNAs can recruit the translation apparatus for decoding, they eventually cause synthesis of erroneous protein products and premature translation termination in rabbit reticulocyte lysate and human HEK-293 cells [157].…”
Section: Mrnas and Trnasmentioning
confidence: 99%